Earth-abundant and nano-micro composite catalysts of Fe3O4@reduced graphene oxide for green and economical mesoscopic photovoltaic devices with high efficiencies up to 9%. Issue 1 (17th November 2015) - Zhou, Huawei; Yin, Jie; Nie, Zhonghao; Yang, Zhaojin; Li, Dongjie; Wang, Junhu; Liu, Xin; Jin, Changzi; Zhang, Xianxi; Ma, Tingli
Abstract : The ideal liquid–solid heterogeneous electrocatalysis should have not only high catalytic activity but also free electron transport. Abstract : The ideal liquid–solid heterogeneous electrocatalysis should have not only high catalytic activity but also free electron transport. However, preparing a single catalyst that simultaneously possesses both advantages has proven to be challenging. Herein, we prepared nano–micro composite catalysts (NMCCs) composed of highly dispersed Fe3 O4 nanoparticles fixed on reduced graphene oxide (RGO) sheets (namely Fe3 O4 @RGO-NMCC) as the counter electrode (CE) in dye-sensitized solar cells (DSCs). Compared with the Fe3 O4 or RGO CE, the Fe3 O4 @RGO-NMCC CE exhibited improved activity and reversibility for the catalytic reduction of triiodide ions (I3 − ) to iodide ions (I − ). Notably, DSCs using rigid and flexible Fe3 O4 @RGO-NMCC CEs achieved high PCEs up to 9% and 8% on fluorine-doped tin oxide (FTO)/glass substrates and flexible polymer substrates, respectively. These values are, to our knowledge, some of the highest reported efficiencies for DSCs based on a flexible Pt-free CE. We ascribed the superior catalytic performance of Fe3 O4 @RGO-NMCC to faster electron hopping between Fe 2+ and Fe 3+ and free electron transport by broad RGO sheets. Finally, Fe3 O4 @RGO-NMCC exhibited good stability in the practical application of DSCs because Fe3 O4 nanoparticles were chemically bonded to the surface of RGO. Our work here will be of great interest for fundamental research and practical applications of Fe3 O4 in lithium batteries, splitting water and magnetic fields.